Everyday memory: towards a translationally effective method of modelling the encoding, forgetting and enhancement of memory. (26th July 2017) - Nonaka, Mio; Fitzpatrick, Richard; Lapira, Jennifer; Wheeler, Damian; Spooner, Patrick A.; Corcoles‐Parada, Marta; Muñoz‐López, Mónica; Tully, Tim; Peters, Marco; Morris, Richard G. M.
Abstract: The testing of cognitive enhancers could benefit from the development of novel behavioural tasks that display better translational relevance for daily memory and permit the examination of potential targets in a within‐subjects manner with less variability. We here outline an optimized spatial 'everyday memory' task. We calibrate it systematically by interrogating certain well‐established determinants of memory and consider its potential for revealing novel features of encoding‐related gene activation. Rats were trained in an event arena in which food was hidden in sandwells in a different location everyday. They found the food during an initial memory‐encoding trial and were then required to remember the location in six alternative choice or probe trials at various time‐points later. Training continued daily over a period of 4 months, realizing a stable high level of performance and characterized by delay‐dependent forgetting over 24 h. Spaced but not massed access to multiple rewards enhanced the persistence of memory, as did post‐encoding administration of the PDE4 inhibitor Rolipram. Quantitative PCR and then genome‐wide analysis of gene expression led to a new observation – stronger gene‐activation in hippocampus and retrosplenial cortex following spaced than massed training. In a subsidiary study, a separate group of animals replicated aspects of this training profile, going on to show enhanced memory when training was subject to post‐encoding environmental novelty. Distinctive features of this protocol include its potential validity as a model of memory encoding used routinely by human subjects everyday, and the possibility of multiple within‐subject comparisons to speed up assays of novel compounds. Abstract : Many aspects of everyday memory are remembered for a few hours and then forgotten. Our new animal model of this type of memory requires rats to discriminate between a rewarded and an unrewarded location of food reward in an event arena. We explore neurobiological parameters that determine how long such memories last, including unexpected environmental novelty given after memory encoding, and the impact of a putative cognitive enhancer.